Adjuvant immunotherapy in renal cell carcinoma: a systematic review and meta‐analysis. (28th February 2023) - Riveros, Carlos; Huang, Emily; Ranganathan, Sanjana; Klaassen, Zachary; Rini, Brian; Wallis, Christopher J.D.; Satkunasivam, Raj
Abstract : Objectives: To synthesise available data regarding the disease‐free survival (DFS) benefit of adjuvant immune checkpoint inhibitors (ICIs) for patients with renal cell carcinoma (RCC) and evaluate the overall safety profile of ICIs in this setting. Materials and Methods: We utilised PubMed, Embase, and relevant conference proceedings to identify phase III randomised controlled trials comparing adjuvant ICIs vs placebo/observation for RCC. The primary outcome of interest was DFS. Variables for subgroup analyses were programmed death‐ligand 1 (PD‐L1) expression, sarcomatoid features, nephrectomy type, and disease‐risk category. Secondary outcomes included Grade ≥3 adverse events (AEs), immune‐related AEs, and treatment discontinuation due to AEs. All outcomes were analysed using random‐effects models owing to inter‐study heterogeneity. Results: Among the four included studies, one demonstrated a significant DFS benefit. There was considerable clinical and statistical heterogeneity ( I 2  = 64%) due to differences in inclusion criteria and interventions. While pooled results across the four studies did not demonstrate a significant benefit in DFS overall (hazard ratio [HR] 0.85, 95% confidence interval [CI] 0.69–1.04) there was significant benefit among patients with positive PD‐L1 expression (HR 0.72, 95% CI 0.55–0.94) and sarcomatoid features (HR 0.59, 95% CI 0.38–0.91). Conclusion: The evidence base to date regarding ICIs as adjuvant therapy in RCC is mixed – conclusions are limited by considerable heterogeneity between studies. However, pooled analyses suggest that patients with positive PD‐L1 expression or sarcomatoid features are most likely to benefit from adjuvant immunotherapy.